YAP1 controls degeneration of human cartilage chondrocytes in response to mechanical tension. (12th July 2022) - Ding, Baiyang; Xiao, Liang; Xu, Hongguang
Abstract: Disc herniation is a kind of disease caused by degenerative discs, which is common in the elderly, bringing substantial financial burden to families and society. Mechanical tension has a vital effect on the maintenance of cartilage function, however, the molecular mechanism by which mechanical tension causes degenerative discs to remain unclear. This study was the first to reveal Yes‐associated protein 1(YAP1) is a key regulator in mechanical tension‐mediated degenerative discs. Activation of YAP1 may be a valuable strategy to delays the degeneration of human cartilage chondrocytes. We found that YAP1 expression was significantly decreased in degenerative human endplate cartilage and tissue with the strength and time of mechanical stimulation, but the cell cycle distribution was significantly changed under the 10% cyclic mechanical tension(CMT). Besides, the degeneration of endplate cartilage can be delayed by activating the expression level of YAP1 in vitro and it has also been verified in the cartilage endplate tissue in vitro. Furthermore, We found that YAP1 and TEAD1 overexpression increased the activity of the ACAN or COL2A1 promoter to enhance the transcriptional activity of human chondrocyte collagen. The CMT activates the classic Hippo signaling pathway of YAP1, and piezo1 may regulate YAP1 expression through the Hippo signaling pathway. In conclusion, these results suggest the novel mechanism of YAP contributes to delaying the degeneration of endplate cartilage and targeting YAP in combination with Piezo1 is a potential therapeutic approach for the treatment of endplate cartilage degeneration.